PROFITABILITY DETERMINANTS OF MILL COMPANIES FROM THE REPUBLIC OF SERBIA - Novaković, Dragana; Novković, Nebojša; Mutavdžić, Beba; Novaković, Tihomir; Vukelić, Nataša; Šarac, Veljko; Nikolić, Srboljub (Journal on Processing and Energy in Agriculture, 2025)
In order to assess the profitability of mill companies and identify influencing factors, 30 companies operating in the Republic of Serbia from 2010 to 2019 were analyzed. The profitability of these companies was measured using the ROA indicator. Internal factors influencing profitability included liquidity, indebtedness, financial leverage, asset structure indicator, total asset turnover ratio, and Z-score, while external factors considered were the gross domestic product growth rate and inflation. The analysis of the collected financial data began with the application of descriptive statistics to gain a clearer understanding of their business performance and the economic environment in which they operate. Following the descriptive statistical analysis, a panel regression method was employed to determine the impact of the observed internal and external factors on the profitability of milling companies. Based on the estimated panel regression model, it was found that the statistically significant factors influencing the profitability of the observed companies include liquidity, financial leverage,tangibility, total asset turnover ratio, Z-score, and inflation. Among these significant factors, only Z-score had a positive impact on profitability, while the other factors negatively affected the profitability of the observed companies.